Review: Diario de campo. Izquierdo Chaparro, R. (2013). Madrid: Caballo de Troya. 144 pp. - Soledad García Gómez (Sociedad Iberoamericana de Pedagogía Social, 2014)
The draft of a qualitative research report is the product of a hard and exciting task that involves a rigorous analysis of data  collected applying such techniques as the interview. To give sense to the textual data collected or to let the meanings of the data arise is a challenge, from the point of view of the scientific community that holds an interpretative or critical research paradigm. The later writing of the final report is also an important task because it will be the testimony or witness of the work done and of all the findings.